2015
DOI: 10.1038/npp.2015.348
|View full text |Cite|
|
Sign up to set email alerts
|

A Selective Nociceptin Receptor Antagonist to Treat Depression: Evidence from Preclinical and Clinical Studies

Abstract: Nociceptin/Orphanin FQ (N/OFQ) is an endogenous ligand of the N/OFQ peptide (NOP) receptor, which is a G protein-coupled receptor in brain regions associated with mood disorders. We used a novel, potent, and selective orally bioavailable antagonist, LY2940094, to test the hypothesis that blockade of NOP receptors would induce antidepressant effects. In this study we demonstrate that targeting NOP receptors with LY2940094 translates to antidepressant-like effects in rodent models and, importantly, to antidepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 50 publications
8
108
0
4
Order By: Relevance
“…Thus, these findings further support a large body of evidence indicating that the blockade of NOP receptors promotes antidepressant-like effects. In fact, the actions of distinct NOP antagonists (i.e., [Nphe 1 ]N/OFQ(1-13)-NH 2 , UFP-101, SB-612111, J-113397, LY2940094) has been well established in behavioral despair tests (Gavioli and Calo' 2013;Post et al 2015). Moreover, it is worth highlighting the studies of Vitale et al (2009) andMedeiros et al (2015) which have demonstrated that the blockade of NOP receptors reversed depressive-like behaviors induced by chronic exposure to an unpredictable sequence of mild stressful stimuli in rats and by the transient inflammatory process elicited by a single administration of lipopolysaccharide in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these findings further support a large body of evidence indicating that the blockade of NOP receptors promotes antidepressant-like effects. In fact, the actions of distinct NOP antagonists (i.e., [Nphe 1 ]N/OFQ(1-13)-NH 2 , UFP-101, SB-612111, J-113397, LY2940094) has been well established in behavioral despair tests (Gavioli and Calo' 2013;Post et al 2015). Moreover, it is worth highlighting the studies of Vitale et al (2009) andMedeiros et al (2015) which have demonstrated that the blockade of NOP receptors reversed depressive-like behaviors induced by chronic exposure to an unpredictable sequence of mild stressful stimuli in rats and by the transient inflammatory process elicited by a single administration of lipopolysaccharide in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these preclinical findings were corroborated by studies performed with the novel NOP receptor antagonist LY2940094 (Toledo et al 2014). This compound induces antidepressant-like effects in rodent models, and more importantly displayed antidepressant efficacy in patients with major depressive disorder (Post et al 2015).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The available information in this specific field was recently reviewed (Gavioli and Calo', 2013). Very recently a double-blind, placebocontrolled trial performed with the novel NOP selective antagonist LY2940094 in patients with major depressive disorder provided the first clinical evidence that the blockade of NOP receptor signaling represents a promising strategy for the treatment of depression (Post et al, 2015).…”
Section: S]mentioning
confidence: 99%
“…Pharmacological blockade of NOP receptors by selective antagonists specifically attenuated the motivation for alcohol in Wt but not in NOP ( − / − ) rats. A novel NOP antagonist with a safe pharmacological profile is currently under investigation for depression in humans (Post et al, 2016). Substance use disorders may possibly represent an additional clinical indication for this compound.…”
Section: Nop Antagonists Attenuate Ethanol Drinking In Wtmentioning
confidence: 99%